Prevalence of anemia and its associated factors among rural adolescent girls in West Badewacho district, central Ethiopia: a community based cross-sectional study - Kebede, Wondimagegn; Hailu, Awoke Girma; Hegena, Tadele; Agde, Zeleke Dutamo (Frontiers in Public Health, 2025)
BackgroundAnemia is closely interconnected with the five global nutrition targets, including stunting, low birth weight, childhood overweight, exclusive breastfeeding, and wasting. However, previous studies in Ethiopia have predominantly focused on populations other than adolescents or have relied on hospital-based surveys with limited geographical coverage, resulting in limited evidence in this segment of the population. This study therefore aimed to assess the prevalence and determinants of anemia among adolescents in the West Badewacho District, central Ethiopia.MethodsA community-based cross-sectional study was conducted among 548 adolescent girls in the West Badewacho district, central Ethiopia, in June 2022. A systematic random sampling technique was employed to select the study participants. Data were collected using a pretested structured questionnaire. A 10 microliter (μL) blood sample was collected from each participant. Data entry and analysis were conducted using EpiData version 4.6 and SPSS version 25, respectively. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were computed and variables with p < 0.05 in the multivariable logistic regression analysis were considered significantly associated with anemia.ResultsThe prevalence of anemia was 25.9% (95% CI: 20.7, 30.1). Among the anemic participants, 17.5% had mild anemia (hemoglobin level 10.0–11.9 g/dL) and 8.4% had moderate anemia (hemoglobin level 8.0–9.9 g/dL). The strongest predictors of anemia were household family size of five or more (AOR: 8.02; 95% CI: 3.97, 16.17), menstrual blood flow lasting 5 days or more (AOR: 7.64; 95% CI: 2.02, 28.94), and lack of intestinal parasite treatment or deworming (AOR: 3.94; 95% CI: 1.63, 9.52). Iron-folate intake during adolescence was found to be protective against anemia (AOR: 0.64; 95% CI: 0.11, 0.93).ConclusionAnemia among adolescent girls was a moderate public health concern in the study area. The strongest predictors of anemia were larger household family size, prolonged menstrual blood flow, and lack of deworming, while iron-folate supplementation was protective. Efforts to reduce anemia should focus on promoting iron-folate supplementation, addressing prolonged menstrual bleeding, improving treatment for intestinal parasites, and providing targeted interventions for larger families.